2005
DOI: 10.1213/01.ane.0000184124.29397.eb
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Evaluation, and Management of Anemia in the Elective Surgical Patient

Abstract: The prevalence of anemia in elective surgical patients may be as frequent as 75% in certain populations. A national audit demonstrated that 35% of patients scheduled for joint replacement therapy have a hemoglobin <13 g/dL on preadmission testing. Standard practice currently consists of preadmission testing 3 to 7 days before an elective operative procedure, precluding the opportunity to effectively evaluate and manage a patient with unexpected anemia. Therefore, a standardized approach for the detection, eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
90
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 14 publications
5
90
0
5
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] Our data confirm that patients in the Pre-Protocol group with Fig. 3 The impact of protocol implementation in anemic (Hb \ 120 gÁL -1 ) and non-anemic patients (Hb [ 120 gÁL -1 ) is demonstrated.…”
Section: Discussionsupporting
confidence: 77%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] Our data confirm that patients in the Pre-Protocol group with Fig. 3 The impact of protocol implementation in anemic (Hb \ 120 gÁL -1 ) and non-anemic patients (Hb [ 120 gÁL -1 ) is demonstrated.…”
Section: Discussionsupporting
confidence: 77%
“…Reports have demonstrated that about 35% of patients undergoing joint arthroscopy or non cardiac surgery have anaemia while about 76% of patients with Dukes stage D colon cancer have low haemoglobin levels before surgery [17][18][19]. Furthermore, previously undiagnosed anaemia is common in elective orthopaedic surgical patients and is associated with increased likelihood of blood transfusion and increased perioperative morbidity and mortality [20].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that there is an increasing interest among health providers for optimizing the management of pre-operative anaemia with the aim of improving outcome and reducing blood transfusion, especially with the current shortage of blood supply. Moreover, many cases of preoperative anaemia are associated with depleted iron stores [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Within a preoperative preparation, anemail etiology should be determined and its treatment should start before the scheduled surgical procedure (3). There are diverse therapeutic options depending on the etiology, such as iron therapy, erythropoietin therapy or autologous transfusion administration such is preoperative autologous blood donation (3,25,26). This would significantly reduce perioperative complications and the length of hospitalization.…”
Section: Discussionmentioning
confidence: 99%